Cartographo-Mathematical Modelling of Landscape Diversity for Land Use Planning Purposes. Issue 1 (October 2020) - Osipov, A; Dmitriev, V; Kovyazin, V; Romanchikov, A
Abstract: It is necessary to increase the informational supply of land-use planning so it causes the significance of investigation. Different cartographic materials are important part of this supply. For reaching this goal, authors developed the method of landscape diversity cartographo-mathematical modelling using GIS-technology. During the process of investigation, we got following results. We developed the method of landscape diversity modelling. We defined indexes describing landscape diversity, including: fragmentation index of natural region enclosures (amount of enclosures by landscape area unit); landscape complexity index (amount of enclosures and natural regions by its average area unit); landscape fragmentation index (ratio of average area of landscape enclosure to landscape area), pattern index (average amount of natural region enclosures to one group); Margalef and Menchinik indexes (relative abundance of natural region groups). We proposed the relationship for landscape diversity integrated index calculation and developed the quality determination scale for its evaluation. We tested the method on the East of Leningrad region including 16 landscapes (grouped to 5 types) and 1876 natural region enclosures. Landscape maps were main materials for investigation. Obtained results of landscape diversity evaluation have no contradictions with other researchers' works.